Delta‐globin gene expression improves sickle cell disease in a humanised mouse model. (28th May 2021) - Porcu, Susanna; Simbula, Michela; Marongiu, Maria F.; Perra, Andrea; Poddie, Daniela; Perseu, Lucia; Kowalik, Marta A.; Littera, Roberto; Barella, Susanna; Caria, Cristian A.; Demartis, Franca R.; Ristaldi, Maria S.
Summary: Sickle cell disease (SCD) is a widespread genetic disease associated with severe disability and multi‐organ damage, resulting in a reduced life expectancy. None of the existing clinical treatments provide a solution for all patients. Gene therapy and fetal haemoglobin (HbF) reactivation through genetic approaches have obtained promising, but early, results in patients. Furthermore, the search for active molecules to increase HbF is still ongoing. The delta‐globin gene produces the delta‐globin of haemoglobin A2 (HbA2). Although expressed at a low level, HbA2 is fully functional and could be a valid anti‐sickling agent in SCD. To evaluate the therapeutic potential of a strategy aimed to over‐express the delta‐globin gene in vivo, we crossed transgenic mice carrying a single copy of the delta‐globin gene, genetically modified to be expressed at a higher level (activated), with a humanised mouse model of SCD. The activated delta‐globin gene gives rise to a consistent production of HbA2, effectively improving the SCD phenotype. For the first time in vivo, these results demonstrate the therapeutic potential of delta‐globin, which could lead to novel approaches to the cure of SCD.